2008
DOI: 10.1099/jmm.0.47385-0
|View full text |Cite
|
Sign up to set email alerts
|

A hospital-wide study of the impact of introducing a personal data assistant-augmented blood culture round

Abstract: Blood culture is the cornerstone of an established aetiological diagnosis of septicaemia. The automated blood culture systems used for this purpose have changed little in the last decade, and the clinical value of results depends on a variety of factors, including pre-and post-analytical variables. Growing scepticism over the value of blood culture results and pressure for the introduction of molecular detection systems have prompted a critical path analysis of pre-, peri-and post-analytical stages in the gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 17 publications
0
13
1
Order By: Relevance
“…This is particularly relevant in internal medicine wards, where multiple comorbidities, severe infectious or non-infectious diseases and complications during hospital stay are frequent. 4,11,12 Our positivity rate is slightly lower than in other series, which can be attributed to the several BC performed in patients with low-severity infection, namely patients who do not meet sepsis criteria. 13 It has been proposed that severity of infection may be the best predictor of positivity of BC, but the way to assess this remains controversial.…”
Section: Discussioncontrasting
confidence: 39%
See 1 more Smart Citation
“…This is particularly relevant in internal medicine wards, where multiple comorbidities, severe infectious or non-infectious diseases and complications during hospital stay are frequent. 4,11,12 Our positivity rate is slightly lower than in other series, which can be attributed to the several BC performed in patients with low-severity infection, namely patients who do not meet sepsis criteria. 13 It has been proposed that severity of infection may be the best predictor of positivity of BC, but the way to assess this remains controversial.…”
Section: Discussioncontrasting
confidence: 39%
“…Recent papers suggest that overuse of BC may be responsible for prolonging hospital length of stay (LoS) and higher hospital costs, without relevant impact on mortality. 4 Direct utility of BC when measured by therapeutic changes based on its results is limited. According to a study by Corbo et al in 355 admissions for community acquired pneumonia, only in 5% of patients the antibiotic was changed based on BC results.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that timeliness of detecting bloodstream pathogens improves antimicrobial therapy, reduces costs, and decreases length of stay and patient mortality. [3][4][5][6][7][9][10][11] Timeliness and accuracy of preliminary blood culture results represent 2 important, evidence-based quality indicators that are closely linked to clinical outcomes.…”
Section: Commentmentioning
confidence: 99%
“…Faster results reporting has been shown to be associated with lower mortality, 3 especially when combined with clinical consultation. 4,5 Other benefits of rapid reporting include improved selection of antimicrobial therapy, [6][7][8][9] lower overall health care costs, 10 and reduced length of stay. 8,11 Timely detection of bacteremia also facilitates initiation of rapid, direct methods for early identification and susceptibility testing.…”
mentioning
confidence: 99%
“…1 It has been inferred from work on commoner bacteremic agents that faster identification of bacteria from blood cultures will result in faster defervescence and other benefits to septicemic patients. 2 In the case of melioidosis, an uncommon cause of septicemia in most centers, progression to multiple organ systems failure and death can be rapid. 3 Some patients who do not immediately die of septicemia can remain bacteremic for several days despite appropriate intravenous antimicrobial chemotherapy.…”
mentioning
confidence: 99%